2019
DOI: 10.3389/fncel.2018.00509
|View full text |Cite
|
Sign up to set email alerts
|

Brain Derived Neurotrophic Factor (BDNF) Delays Onset of Pathogenesis in Transgenic Mouse Model of Spinocerebellar Ataxia Type 1 (SCA1)

Abstract: Spinocerebellar ataxia type 1 (SCA1) is a fatal neurodegenerative disease caused by an abnormal expansion of CAG repeats in the Ataxin-1 (ATXN1) gene and characterized by motor deficits and cerebellar neurodegeneration. Even though mutant ATXN1 is expressed from an early age, disease onset usually occurs in patient’s mid-thirties, indicating the presence of compensatory factors that limit the toxic effects of mutant ATXN1 early in disease. Brain derived neurotrophic factor (BDNF) is a growth factor known to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 63 publications
4
37
0
Order By: Relevance
“…Although it has been demonstrated that BDNF play a role in cerebellar neuropathology in SCA1 40 , the hippocampal BDNF deficiency that we determined has not been described in any other SCA animal model to date. Since BDNF plays an important role in neurite growth, neuronal survival and neurogenesis [41][42][43] , we speculate that BDNF deficiency may partially contribute to the hippocampal neuropathology described above and may represent a hopeful target for hippocampal-focused SCA1 therapy.…”
Section: Discussionmentioning
confidence: 59%
“…Although it has been demonstrated that BDNF play a role in cerebellar neuropathology in SCA1 40 , the hippocampal BDNF deficiency that we determined has not been described in any other SCA animal model to date. Since BDNF plays an important role in neurite growth, neuronal survival and neurogenesis [41][42][43] , we speculate that BDNF deficiency may partially contribute to the hippocampal neuropathology described above and may represent a hopeful target for hippocampal-focused SCA1 therapy.…”
Section: Discussionmentioning
confidence: 59%
“…These results are suggestive of the first neuroprotective role played by astrocytes in SCA1 pathogenesis, which becomes harmful later on. Very recently, an early increase in the expression of brain-derived neurotrophic factor (BDNF) was identified as a key mediator of the initial neuroprotective role of astrocytes: an early delivery of this factor is indeed capable of delaying motor impairments and PCs pathology in a SCA1 mouse model [77]. Whether a biphasic role of astrogliosis in the disease onset also holds true for other kinds of ataxia is still needs to be elucidated.…”
Section: Astrogliosis: An Early Point Of No Return?mentioning
confidence: 99%
“…Importantly, although a bi-phasic role of astrogliosis in ataxia pathophysiology has been so far suggested only for SCA1, these treatments may need to consider the stage of disease progression to achieve therapeutic efficacy. In a first phase of the disease, when astrocytes' reactivity may be protective [76], the inhibition of astroglial NF-κB signaling, likely effective at later stages [58], may indeed result detrimental, while BDNF delivery may delay disease onset fostering astrocytes' defensive role against neurotoxicity, at least in SCA1 [77]. Similarly, even stimulating BG/astrocytes proliferation at this stage could be a viable therapeutic intervention [118].…”
Section: Treating Astrocytes To Heal Neurons: New Promising Approachementioning
confidence: 99%
“…Complicated SPG-30 may include cerebellar dysfunction typically characterized by ataxias as cerebellar neurons would be affected similarly to other cell types by the lack of BDNF (Carter et al, 2002). In fact, Mellesmoen et al (2019) recently demonstrated that endogenously applied BDNF can delay cerebellar dysfunction onset in mouse models of ataxia. Cognitive deficits arising in complicated HSPs may be explained by similar mechanisms.…”
Section: Kif1a Cargosmentioning
confidence: 99%